2021
DOI: 10.3389/fphar.2021.809467
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Tumour Lysis Syndrome Induced by Brigatinib in a Lung Adenocarcinoma Patient Treated With Sequential ALK Inhibitors: A Case Report

Abstract: Tumour lysis syndrome (TLS) represents a group of fatal metabolic derangements resulting from the rapid breakdown of tumour cells. TLS typically occurs soon after the administration of chemotherapy in haematologic malignancies but is rarely observed in solid tumours. Here, we report a case of brigatinib-induced TLS after treatment with sequential anaplastic lymphoma kinase (ALK) inhibitors in a patient with advanced ALK-rearranged lung adenocarcinoma. The patient was treated sequentially with crizotinib, alect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…However, for the present case, the response to ensartinib only lasted for one month, which indicated that E803Q might be resistant to ensartinib. Similarly, for the case reported by Wang et al, ensartinib only achieved SD for patients who relapsed from alectinb treatment with multiple secondary mutations, including L1196M, G1269A, F1174L, and V1180L, and the PFS for ensartinib was only four months 17 . It has been demonstrated that the V1180L mutation is still sensitive to ceritinib in preclinical studies 11,16 .…”
Section: Case Reportmentioning
confidence: 51%
“…However, for the present case, the response to ensartinib only lasted for one month, which indicated that E803Q might be resistant to ensartinib. Similarly, for the case reported by Wang et al, ensartinib only achieved SD for patients who relapsed from alectinb treatment with multiple secondary mutations, including L1196M, G1269A, F1174L, and V1180L, and the PFS for ensartinib was only four months 17 . It has been demonstrated that the V1180L mutation is still sensitive to ceritinib in preclinical studies 11,16 .…”
Section: Case Reportmentioning
confidence: 51%
“…We have identified seven previous reports of the occurrence of TLS in patients with pulmonary adenocarcinoma [9,10,[16][17][18][19][20]. All seven patients had metastatic disease: four had liver metastases and four had lymph node involvement.…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of TLS in association with targeted therapy is very rare. Furthermore, few cases of TLS have been identified in patients with pulmonary adenocarcinoma receiving targeted agents, such as EGFR-TKIs and ALK-TKIs [9,10]. Only two cases of TLS have been identified in patients with pulmonary adenocarcinoma receiving targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations